PHYTOCHEMICAL SCREENING, ANTIOXIDANT ACTIVITY AND EXTRACTION OF ACTIVE COMPOUND (ANONAINE) FROM FRUIT PEEL EXTRACT OF ANNONA RETICULATA L. - Ethiraj, Sumathi; Sridar, Vandana (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objective: The main objective of this study was to analyze the phytochemical constituents, total phenol, total flavonoid, alkaloid content, in vitro antioxidant activity and high-performance liquid chromatography (HPLC) analysis of anonaine compound from the fruit peel extract of Annona reticulata L. Methods: Preliminary phytochemical analysis for alkaloids, cardiac glycosides, flavonoids, glycosides, phenols, saponins, steroids, tannins, and terpenoids was studied. Quantitative phytochemical analysis for total phenolics, total flavonoids and alkaloids was determined according to standard protocols. In vitro antioxidant potential was evaluated by assessing 1,1-diphenyl-2-picrylhydrazyl (DPPH) radical scavenging activity by following standard procedure. HPLC analysis was carried out to identify a major metabolite, namely, anonaine compound from fruit peel extract of A. reticulata L. Results: Phytochemical screening of various extracts such as aqueous, ethanol, chloroform, acetone, and petroleum ether of fruit peel extracts revealed the presence of tannins, saponins, phenols, flavonoids, cardiac glycosides, coumarins, terpenoids, alkaloids, and steroids. Total phenol, flavonoid and alkaloid contents were quantitatively estimated which recorded maximum in Ooty accession (17.75±0.13 mg gallic acid equivalents/g, 13.97±0.21 mg quercetin equivalents/g, and alkaloid content of 6.92±0.14 mg/g), respectively. Among three accessions with five different solvents used, maximum antioxidant activity was found in aqueous peel extract (90.76±1.3%) from Ooty accession followed by others. The results of HPLC analysis in the fruit peel extract of A. reticulata proved the presence of the active principle, namely anonaine compound. Conclusion: Therefore, this study suggests the possibility of using fruit peel extracts of A. reticulata as a potent source of natural antioxidant and thus could prevent many free radical mediated diseases. The validated HPLC method can be used for routine quality control analysis.